Entangled in structural and cultural barriers? a case study on women’s leadership practices in the university / Nurzahirah Mohd Ayob …[et al.] - Mohd Ayob, Nurzahirah; Shahidani, Nur Adilah; Hassan, Farihah; Ahmad, Saidah Hamizah; Abu Hasan, Norraidah (Universiti Teknologi MARA, 2020)
The Glass Ceiling issue in a business case contributes to women remain disproportionately underrepresented in management positions. This study believes that structural and cultural barriers are the main blocks inhibiting their advancement in the corporate ladder. This paper provides an analysis of structural and cultural as an indicator of women’s leadership in university. It discovers that women appear to be more likely as leaders in structural than cultural setting. Hence, this paper reveals the vital role of an organisation to promote women in leadership positions by employing strategies that are compatible with the culture’s tightness.